Legal Protection Of Prisoners Who Fight (Research study in Class 1 Medan Detention Center) - Muhammad Guntur Perkasa; Syaiful Asmi Hasibuan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The Detention Center is a place of development for correctional students and students who is serving his sentence. Coaching is carried out so that activities become distant individuals better, but as time goes by, there are so many correctional institutions that haven't can the responsibility of creating a peaceful Detention Center still be many. who do fights in the prison inmates who do fights in In the Medan 1st Class Detention Center, there are quite a lot of them. Coaching towards awards in the detention house has been done maximally by the officers and even punishment for the law those who fight in the Correctional Institution are also in accordance with their proper portion makes it a deterrent and doesn't want to repeat his actions again, but that's not all feel deterred from the punishment that has been given by the prison officers not even a little too Those who are still repeated among them without fellow humans.